PENINGKATAN PRESTASI BELAJAR ILMU PENGETAHUAN ALAM MELALUI MODEL CONTEXTUAL TEACHING AND LEARNING DI SEKOLAH DASAR - Bayu Purbo Asmoro; Fajar Dwi Mukti (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2019)
This study presents an increase in natural science learning achievement through the CTL model in class VA students at Karangroto 02 State Elementary School. The research method used in this research is Classroom Action Research (CAR). This research is planned for two cycles, namely cycle I and cycle II, if it is not successful it will be continued in the next cycle. The CAR method used in this study is the CAR method according to Kemmis and Mc Taggart which uses a reflection spiral system consisting of several cycles. In the Kemmis and Mc Taggart methods it is explained that in one cycle or round consists of four components, namely planning, acting, observing and reflecting. Data collection techniques used are observation, interviews and documentation. The results showed that, in the first cycle, the classical percentage was 32.5% with an average class of 58, while the second cycle obtained 87.5% classical completeness with an average class of 70. It can be concluded that the Contextual Teaching and Learning Model can improve learning achievement. Science class Va elementary school students.